Pengangguran di Provinsi Banten: Determinan dan alternatif kebijakannya - Muhammad Ernanda; Manuntun Parulian Hutagaol; Zulva Azijah (Jurnal Ekonomi dan Pembangunan, 2025)
This study has two aims. First, find and understand the root cause of the high unemployment rate in Banten Province. Second, formulate alternative policies that need to be carried out by the government to facilitate the reduction of the unemployment rate in Banten Province. The method used in the form of quantitative analysis using panel data regression equation with the Fixed Effect Model (FEM) approach. The estimation results of the model given by the White Robust Standard Error show that in-migration is the only variable that has a significant effect by causing an increase in the unemployment rate. The alternative policies that can be implemented to solve the problem of unemployment in Banten Province are the development of incentive-based labor-intensive industries in the northern region, development of the agricultural sector based on technology and infrastructure in the southern region, and job creation through the development of the informal secto